MENGATASI KENAKALAN ANAK MELALUI HUKUM PIDANA: EFEKTIVITAS DAN KEADILAN - Jayadi, Usman; Isro'iyah, Latifatul (Berajah Journal, 2024)
Child delinquency is a complex social problem and requires appropriate handling so that it does not lead to negative impacts on the future of children and society. This article discusses the effectiveness of criminal law in dealing with juvenile delinquency, as well as the challenges and justice that arise in the law enforcement process. By examining various legal approaches, including restorative justice, this article analyzes how the legal system can function as an effective rehabilitation tool, rather than simply a means of punishment. Existing case studies and literature show that handling child delinquency must consider social and psychological aspects, as well as strengthening the role of the family and community. The results of this research emphasize the importance of policies that support child rehabilitation as preventive and healing measures that are more effective than retributive approaches. Thus, justice in criminal law is not only focused on punishment, but also on the recovery and reintegration of children into society.